Flexible Magnetostrictive Nanocellulose Membranes for Actuation, Sensing, and Energy Harvesting Applications - Yermakov, Aleksey; Thompson, Andrew; Coaty, Christopher; Sabo, Ronald; Law, Chiu Tai; Elhajjar, Rani (Frontiers in Materials, 2020)
Magnetostrictive composite known as magnetostrictive nanocellulose membrances (MNMs) were fabricated by embedding Terfeonol-D particles into cellulose nanofibers (CNF). MNMs inherit flexibility and biodegradability from CNF while exhibiting magnetomechanical responses; as such, the valuable rare-earth (Terfenol-D) particles can be recycled. Various orientations of the Terfenol-D particles were induced in the MNMs, and those with in-plane alignment showed the strongest magnetostrictive effect but the lowest Villari effect. Materials with such a unique combination of properties dovetail nicely with Internet of Things that require ubiquitous sensing, actuation and energy harvesting in one package.